Perilla seed oil high internal phase emulsion improve the gel properties of myofibrillar protein - Beibei Li; Yang Wang; Shuyu Wang; Sengao Chen; Chaoyue Yang; Linggao Liu; Shenghui Bi; Ying Zhou; Qiujin Zhu (Food Chemistry: X, 2024)
The effects of perilla seed oil high internal phase emulsions stabilized by pea protein (PP-PSO HIPEs) on the gel properties and conformation of myofibrillar protein (MP) gels were investigated. The results showed that the PP-PSO HIPEs with 4.0 % (w/v) PP formed stable HIPEs with low droplet size and good viscoelasticity. The addition of PP-PSO HIPEs (5.0 % − 15.0 %) could significantly improve the MP gel properties (P < 0.05), while the addition of 10.0 % PP-PSO HIPEs showed the highest gel strength and water holding capacity. Otherwise, the MP gels with 10.0 % PP-PSO HIPEs showed higher proportions of immobile water (PT22) and lower proportion of free water (PT23), and the Raman spectra suggested that the content of α-helix decreased, while the content of β-sheet increased (P < 0.05), thus facilitating the formation of better gel properties. Therefore, the addition of PP-PSO HIPEs is a potential alternative for developing fat-reduced meat products.